Brunner & Suddarth's textbook of medical-surgical nursing - Hinkle, Janice L.; Cheever, Kerry H. (2014)
"This textbook has been a favorite resource for students, instructors, and practicing nurses for almost a half-century. It's comprehensive yet accessible approach covers a broad scope of medical conditions while focusing strongly on the nurse's role in caring for, educating, and assisting patients and families"--Provided by publisher.
Preceded by Brunner & Suddarth's textbook of medical-surgical nursing / Suzanne C. Smeltzer ... [et al.]. 12th ed. c2010.
Keywords: Nursing Care; Perioperative Nursing